Purification of The Tax Court: Reconstructing A Final and Binding Arbitration Model Within an Independent Tax Law Regime - Riztiar Arinta; Megawati Barthos (Jurnal Sosial Teknologi, 2026)
This study aims to reconstruct the ideal design of the Indonesian Tax Court through the approach of tax law as a systematic lex specialis and a self-contained regime. Current Tax Court practice, which permits Reconsideration (Peninjauan Kembali or PK) before the Supreme Court, is deemed to have transformed an extraordinary legal remedy into a conventional final tier, thereby prolonging uncertainty surrounding the State Revenue and Expenditure Budget (APBN). Through a normative legal research method employing conceptual and comparative approaches across several jurisdictions, namely the United States, Germany, the Netherlands, and Malaysia, this analysis finds that tax disputes should ideally be resolved through a mechanism similar to specialized arbitration, presided over by judges with specific taxation expertise. The results recommend a strict separation of forums: judicial review of regulatory norms should be delegated to the Constitutional Court or the Supreme Court, while disputes over facts and tax assessments should be resolved in the Tax Court on a final and binding basis without further legal remedies. The institutional transition of the Tax Court toward a one-roof system under the Supreme Court, following Constitutional Court Decision Number 26/PUU-XXI/2023, must be interpreted as momentum for the purification of judicial authority. This article offers a concrete blueprint for legislators to amend the Tax Court Law by eliminating the Reconsideration avenue and strengthening the oversight of specialized tax judge.